KEBUTUHAN DAN PENGEMBANGAN PEMBELAJARAN DENGAN TEKNOLOGI INFORMASI (E-LEARNING) DI FAKULTAS ILMU KESEHATAN UNIVERSITAS RESPATI YOGYAKARTA - , sukismanto ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The development of information and communication technology has provided a positive effect on the world of education. Elearning is a teaching method that is applied in education and was designed in the Health Science Faculty of Respati University in Yogyakarta, but now there are no e-learning that can be used to support learning. E-learning applications can be designed to suit the needs of its capabilities at the Health Science Faculty of Respati University in Yogyakarta. Method: Action research study design. The sample stage of diagnosing and planning actions taken by managers and lecturers a purposive sampling techniques, sample student with cluster of random sampling. The samples on the stage taking and evaluating the action taken with the technique of convenience sampling. Data analysis in this research is the descriptive analysis of qualitative and quantitative. The size of the validity of the data is performed using the method of triangulation. Results and Discussion: Availability of hardware and software technology has been ready to support the use of information technology but to the readiness of the means by which the user has not all ready for 8.4% of the students, while teachers are all using computers. Availability of computer technology that has not been 100% owned e-learning can be inhibited. Ability to use internet software contained 2.9% of students who can not, a lecturer are 2.0%. Tools used are downloading, uploading, quizzes, assignments and discussions. Users agree as much as 99% if the e-learning design be used to support of learning. Conclusions and suggestions: Needs of e-learning course is suitable as a supporting curriculum applies. Menu e-learning is a download, upload content, quizzes, assignments and discussion. Hardware software technical support has been prepared but not yet all ready user readiness. Evaluation design e-learning accessible, engaging, and agree if applied as complementary learning with some improvement suggestions.